Final report of ENGAGE ‐ Establishing Next Generation sequencing Ability for Genomic analysis in Europe. Issue 6 (29th June 2018) - Hendriksen, Rene S.; Pedersen, Susanne Karlsmose; Leekitcharoenphon, Pimlapas; Malorny, Burkhard; Borowiak, Maria; Battisti, Antonio; Franco, Alessia; Alba, Patricia; Carfora, Virginia; Ricci, Antonia; Mastrorilli, Eleonora; Losasso, Carmen; et al.
Abstract : The ENGAGE project (http://www.engage-europe.eu/ ) was a collaboration between eight institutions across Europe. The aim was to boost the scientific cooperation to use whole genome sequencing (WGS) analysis in food safety and public health protection. ENGAGE focused on Escherichia coli (commensal E. coli ) and different Salmonella spp. serotypes. A total of 3, 360 genomes, 778 and 2, 582 of E . coli and Salmonella, respectively, were produced. These genomes were stored and shared among partners in a temporary repository to be submitted to the European Nucleotide Archive by the end of the project. Generated genomes were used for benchmarking exercises to assess the possibility of replacing conventional typing with WGS for outbreak investigation. For the analysed strains, the benchmarking exercises showed that SPAdes assembly performed better than Velvet and that, by using different bioinformatics tools, WGS Salmonella serotyping and antimicrobial resistance genes detection, were largely in concordance with phenotypic data. Discrepancies were related to sequence quality and phenotype misclassification rather than to limitations of the bioinformatics tools. All partners were able to infer the expected phylogeny for the Salmonella and Campylobacter isolates in benchmarking exercises. Two WGS proficiency tests (assessing different genomic quality markers) were conducted among partners with satisfactory results. Guidelines including available bioinformatics tools and standard operating procedures (wet and dry lab) were prepared and posted online. Workshops, training courses and twinning programmes were conducted. The training focused on online, Galaxy‐based, and command line bioinformatics tools. To reach out beyond ENGAGE, an e‐learning course (17 videos) was developed and made available online. Several proof of concept projects were run and some outcomes published, e.g. the discovery of colistin resistance gene, mcr ‐5. Overall, the project showed that laboratories without previous WGS experience need a period of time to implement and perform WGS for foodborne pathogens routine analysis. All developed material will remain available on the ENGAGE website.